Rural Judges and Territorial Organization in Río de la Plata (17th to 19th Centuries) - Barriera, Dario Gabriel (2016)
This paper focuses on some traces of the challenge of the government of the dispersed populationinto a larger territory of the Spanish Monarchy throughout 16 - 19 century. The main subject is thecreation and implementation of a minor justice: the ?alcalde de la santa hermandad? (judge of thebrotherhood). This rural judge appeared early at Santa Fe and Buenos Aires and plays like an articulatorbetween urban and rural populations. Based on a large base of research, this work showswhat was the role that the office holders allowed to play in the political process equipment planningat the Gobernación of Buenos Aires.